BEYOND ALLIANCE FOR KNOWLEDGE FROM HAMK’S POINT OF VIEW - Puusaari, Pertti; Ahokallio-Leppälä, Heidi; Salminen, Janne (Revista Prâksis, 2019)
ABSTRACT Long term cooperation that is based on common trust, friendship and especially willingness to go forward together is a good basis for development of an international university. Challenging the modern world together makes it possible to reach goals beyond the average. This is the heart of the Beyond Alliance for Knowledge—an alliance between Feevale University, VIA University College and Häme University of Applied Sciences (HAMK). This article is written to highlight the basic needs for the Beyond Alliance for Knowledge from HAMK’s perspective. The perspectives are (1) the need for internationalisation of the university itself, (2) better education products for students and (3) effective research results for businesses and society. The ultimate goal in this alliance should be to develop competences which we need to challenge global wicked problems. Keywords: Alliance. Education. Competence. Co-operation. Research. RESUMO A cooperação de longo prazo, baseada na confiança comum, na amizade e especialmente na disposição de avançar juntos, é uma boa base para o desenvolvimento de uma universidade internacional. Desafiando o mundo moderno juntos, é possível alcançar objetivos além da média. Este é o coração da Beyond Alliance for Knowledge - uma aliança entre a Universidade Feevale, a VIA University College e a Häme University of Applied Sciences (HAMK). Este artigo foi escrito para destacar as necessidades básicas da Beyond Alliance for Knowledge na perspectiva da HAMK. As perspectivas são (1) a necessidade de internacionalização da própria universidade, (2) melhores produtos de educação para os estudantes e (3) resultados efetivos de pesquisa para empresas e sociedade. O objetivo final desta aliança deve ser o desenvolvimento de competências que precisamos para desafiar os complexos problemas globais. Palavras-chave: Aliança. Educação. Competência. Cooperação. Pesquisa.